DINAMIKA PENGANGKUTAN DI BANYUMAS PADA ERA MODERNISASI TRANSPORTASI PADA AWAL ABAD KE-20 - Purnawan Basundoro (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2008)
Transportation in a number of ways is a very effective media to support a region’s progress. When infrastructure of transportation is modernized resulting in a more effectiveness and wellness, all related sectors will under go similar ways. In the end of 19th century to early 20th century modernization of transportation of Banyumas Residency with the establishment of “trem” transportation effects a more mobility of goods and people. More effects show the more openness of the Banyumas Residency and surrounding areas. Market networking is created, inter-regions communication is becoming well, and human mobility is realitively high. Accordingly the well-running transportation has encouraged a region which is previously isolated to be strongly exposed to the world, and this means progress.